Estratégia Científica 2016-2015 - Instituto Nacional da Saúde - Moçambique (Instituto Nacional da Saúde - Moçambique, 2017)
A presente Estratégia Científica do Instituto Nacional de Saúde (INS) para 2016-2025 está alinhada com o Programa Quinquenal do Governo (2015-2019) e com o Plano Estratégico do Sector Saúde (PESS 2014-2019). No contexto global, a elaboração da presente Estratégia teve em conta os Objectivos de Desenvolvimento Sustentável (ODS), o Regulamento Sanitário Internacional (RSI) e a Agenda Global de Segurança Sanitária (GHSA). As principais diferenças entre a presente e anterior estratégia do INS são: 1) um horizonte temporal incrementado, sendo de 10 anos ao contrário de 5 anos na estratégia anterior; 2) uma ampliação das áreas programáticas estratégicas; 3) a inclusão de um robusto eixo estratégico de fortalecimento na área de gestão institucional. A Estratégia Científica do INS 2016-2025 está organizada em Programas e em Eixos Estratégicos. Os oito Programas desta Estratégia Científica reflectem as áreas temáticas consideradas como prioritárias. Estes Programas são: 1) Saúde e Ambiente, incluindo Saúde do Trabalhador; 2) Saúde Mental, Trauma e Violência; 3) Saúde da Mulher e da Criança; 4) Adolescente, Idoso e Outras Populações Vulneráveis; 5) Determinantes de Doenças Crónicas; 6) Doenças Transmitidas por Vectores, Negligenciadas e Zoonóticas; 7) Doenças Endémicas de Grande Impacto Sanitário; 8) Sistema de Saúde. Os cinco Eixos Estratégicos representam as funções essenciais de saúde pública. Este Eixos Estratégicos são: 1) Observatório Nacional de Saúde e Vigilância Epidemiológica; 2) Rede de Laboratórios de Referência em Saúde; 3) Pesquisa, Desenvolvimento Tecnológico e Inovação; 4) Ensino, Informação e Comunicação em Saúde; 5) Gestão e Desenvolvimento Institucional. Cada Programa e Eixo Estratégico tem um ou mais Objetivos Estratégicos e seus respectivos indicadores de impacto, cada um dos quais descreve a situação ideal que se pretende atingir a médio e longo prazo. Cada Objectivo Estratégico deve ser atingido mediante a execução de uma ou mais Acções cujo enunciado reflete num conjunto de Projectos/Actividades afins. Os Projectos são actividades com objectivos e temporalidade definidas, enquanto se denominam Actividades aquelas outras que são de carácter continuado, geralmente de gestão. Finalmente, cada Projecto/Actividade tem Produtos, Indicadores e Metas temporais e/ou quantitativas definidas. Os Projectos/Actividades temáticos encontram-se descritos em cada um dos oito programas, enquanto os Projectos/Actividades estruturantes encontram-se descritos em cada um dos cinco eixos estratégicos. A presente Estratégia Científica compreende 17 Objectivos Estratégicos, 19 Acções e 102 Projectos / Actividades.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - health services / serviços de saúde

Perspectives on the coordination of multisectoral nutrition in Mozambique and an emerging framework - Michaud-Létourneau, Isabelle; Pelletier, David Louis (Food Policy, 2017)
Multisectoral approaches represent a prominent ideological consensus, inﬂuenced by historical roots and the current political, ﬁnancial and institutional landscape, to address the multi-faceted and complex causes of most nutrition, public health and food problems. However, the implementation of multisectoral approaches presents tremendous challenges; one of the most often cited problems, in the literature and by practitioners, is coordination. This study investigates the perspectives of key national leaders on a range of issues regarding the coordination of a Multisectoral Action Plan for the Reduction of Chronic Undernutrition (PAMRDC) in Mozambique. Within this policy group, the principal researcher played the role of a researcher-participant for 14 months, and used Q methodology with a total of 21 key national leaders who had been actively engaged in coordination groups at the central level. Participants sorted 54 subjective statements on a range of issues that were present in the current national discourse. The results revealed four distinct perspectives. The Implementation perspective (n = 12) prioritized concrete actions to advance the operationalization of the plan, based on a guidance-based approach from the central level to the lower administrative levels. The Advocacy perspective (n = 3) emphasized advocacy to increase politicians’ awareness of the problem and of potential solutions to enhance political commitment. The Structuralist perspective (n = 3) was concerned with the development of structures and mechanisms to facilitate coordination, funding and improving communication between the government and donors. The People-centered perspective (n = 3) focused on the importance of mobilizing individuals to compensate for the sub-optimal structures and processes for coordination. Areas of convergence across the perspectives included: low capacity and skills that limit the work; the agency in charge of coordination (SETSAN) should exercise an increased leadership to facilitate the multisectoral work; and SETSAN should advocate to mobilize politicians and donors for resources. Areas of divergence related to the type of guidance from national to sub-national levels (prescriptive or not) and the functions to be carried out by SETSAN. This study highlights lack of clarity on the meaning of coordination and on the functions of the multisectoral coordination body that appear to arise for two reasons: the lack of an explicit and shared framework for the policy process and the complex nature of coordination itself. These results are examined through the lenses of several related literatures, including governance, public policy and political economy of nutrition, leading to a three-dimensional conceptual framework for coordination that distinguishes the coordination space, forms, and instruments. Global guidance, such as provided through the SUN movement, could support countries in overcoming their coordination challenges by facilitating an analysis of their decision-making processes in order to choose the functions for the coordination body based on a shared understanding of countries’ needs, context and opportunities. This paper moves the ﬁeld beyond a broad consideration of horizontal and vertical coordination within multisectoral initiatives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

A Economia Política da Descentralização em Moçambique: Dinâmicas, Efeitos, Desafios - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
O livro aborda a questão da descentralização mediante uma abordagem multidisciplinar e multissectorial, considerando o ângulo visual de tipo político, assim como institucional, da administração pública ou da burocracia, da economia, das finanças (públicas) e da sociedade. O objectivo que se põe tem a ver com o relacionamento entre descentralização e democracia. Trata-se de um assunto conhecido e enfrentado várias vezes no debate próprio da ciência política: será que uma maior descentralização corresponde a um nível mais avançado de democracia? Moçambique é um País ainda novo, quanto à sua vida democrática. E o livro oferece um quadro claro da história da descentralização desde 1992 até hoje; entretanto, a tese de fundo é a seguinte: a classe política que sempre esteve no poder procurou sistematicamente travar ou limitar os processos de descentralização. Será que esta tese é aceitável? Será, sobretudo, que esta tese sai comprovada das evidências que o livro traz?
OCLC: 1062395381
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental